PROFITABILITY ANALYSIS OF LONZA GROUP LIMITED - Kumar, B. Ravi; Sreedevi, K. (IJRDO - Journal of Business Management, 2015)
This paper is an endeavor to portray the profitability position of Lonza Group Limited. This case study is entirely based on secondary data. The data has been gathered from the annual reports of the company from 2009-2013. There are so many ratios that are available to analyze the profitability position of a company. In this study few ratios like Gross Profit Ratio, operating Profit Ratio, Net Profit Ratio, Return on Net worth (RONW) etc., were taken to determine the profitability position of Lonza group Ltd.